Pengaruh Streaming Musik Terhadap Industri Musik di Indonesia - Noviani, Dini; Pratiwi, Raenita; Silvianadewi, Silvia; Benny Alexandri, Mohammad; Aulia Hakim, Marsha (JURNAL BISNIS STRATEGI, 2020)
Music streaming service has become one of the most influential factors in Indonesian music consumption patterns where the music industry can no longer depend on physical products and consumers are now more selective in enjoying music. This study discusses how the development of the use of steaming music platforms has an impact on consumption patterns and music marketing. The method used in this study is a qualitative method by means of descriptions in the form of words and language. The results of this study indicate that the movement of Z as the main connoisseurs of digital music in Indonesia has shown that the music industry players are very supportive of digitalization to facilitate marketing their music and help protect their intellectual property by reducing piracy.